PENGARUH KUALITAS PRODUK, PROMOSI, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK CLOSE UP PADA MAHASISWA STIE YKP YOGYAKARTA - Sudaryanto, Sudaryanto; Novita beri luki, Cindi (PRIMA EKONOMIKA, 2026)
This study aims to determine the influence of Product Quality, Promotion, and Brand Image on the Purchase Decision of Close Up Products among STIE YKP Yogyakarta students. This research is a survey study with a quantitative approach. The population in this study was 200 students who had used Close Up products. The sampling technique used was Non-Probability Sampling, with a sample size of 67 respondents. The research data included primary and secondary data. Data collection was conducted using an online Google Form questionnaire via the link https://forms.gle/FE8Qu65zBjHCvDzh8, which was distributed through WhatsApp. Data analysis included Research Instrument Testing, Classical Assumption Test, t and F Hypothesis Testing, Multiple Linear Regression Analysis, Correlation Coefficient Test (R), and Determination Coefficient Test (Adjusted R Square). The analysis tool used was SPSS version 23. The t-test results partially showed that Product Quality (sig. value 0.017 < 0.05), Promotion (sig. value 0.007 < 0.05), and Brand Image (sig. value 0.005 < 0.05) had a significant influence on the Purchase Decision of Close Up Products among STIE YKP Yogyakarta students. The F-test results (sig. value 0.000 < 0.05) indicated that Product Quality, Promotion, and Brand Image simultaneously had a significant influence on the Purchase Decision of Close Up Products among STIE YKP Yogyakarta students. The correlation coefficient (R) calculation for Product Quality, Promotion, and Brand Image was (0.656), which means the relationship between Product Quality, Promotion, and Brand Image and the Purchase Decision of Close Up Products among STIE YKP Yogyakarta students is categorized as strong. In addition, the coefficient of determination (Adjusted R Square) was (40.4%), indicating the ability of Product Quality, Promotion, and Brand Image variables to explain the variation in the Purchase Decision of Close Up Products among STIE YKP Yogyakarta students, while the remaining 59.6% was influenced by other factors not examined in this study. Keywords: Product Quality, Promotion, Brand Image, Purchase Decision